Quality-Based Principal's Leadership A Site Study At SDN Petompon 2 Semarang, Educational Official Technical Implementation Unit Gajahmungkur Semarang - Rusmini, Rusmini (2012)
There are three objectives of this research. The first is describing the characteristic of the quality-based Principal leadership at SDN Petompon 2 Semarang. Secondly, it is describing the characteristic of the implementation of the quality-based Principal leadership at Public elementary School of 2 Petompon Semarang. Finally, the research aims at classifying the characteristic of the quality-based principal leadership result in SDN Petompon 2 Semarang. It is a qualitative study conducted at SDN Petompon 2 Semarang. The main subject was principal and teachers. The data are people, event, document and artifact. Data collection technique used observation, interview, and documentation. Data anlysis technique used data collection, data reduction, data display, and conclusion. Data validity included credibility, transferability, dependability, dan confermability. The results of this study are (1) the qualified principal leadership can be seen from the activities conducted in the school that is his success in managing the academic and non academic activities; his ability in planning of school activities such as determining the school programs, formulating the school policies, creating the school program and formulation of the steps to do those programs; his ability to organize activities such as having the ability to place the teachers based on their potential and capabilities in teaching and learning activities; his ability to do several activities, such as being able to motivate teachers in the implementation of school programs; and his ability to control his activities that is to evaluate the implementation of school programs, to evaluate the performance of teachers and other personnel. (2) The work program that has been done by the Principal of SDN Petompon 2 Semarang includes in academic program such as the implementation of supervision in learning activity, giving an additional time for the fifth and sixth grade students, doing a preparation for students that join a subject competition and achievement student. In non academic program, the principal holds an extracurricular to improve students' ability in Sport and Art. In organization, the principal conducts an administrative supervision and learning administration. In mobilization activity, the principal can motivate his subordinates. And in controlling activity, the principal always supervise all school members regularly every month. And (3) the result of principal leadership based quality at SDN Petompon 2 Semarang can be seen from the achievement of students and teachers. The program of life skill development that consists of sport, art, and skill can bring students to achieve several achievement in district level, regency, provincial and national level. The program of teacher's professional improvement through giving a motivation that is done by the principal can improve the discipline of teacher and make teachers improve their teaching activity.